2022
DOI: 10.30541/v40i4iipp.519-533
|View full text |Cite
|
Sign up to set email alerts
|

Redistributive Effects of Fiscal Policy across the Income Groups in the Urban-Rural Areas of Pakistan

Abstract: There exist a large number of studies related to the estimates of government budgetary redistributive effects and its related problems with regard to different countries of the world.1 Studies of the impacts of government expenditures and taxes in Pakistan have been conducted within the framework of either incidence of taxes or the impact of expenditures across the income groups. The studies carried out by Azfar (1972); Jeetun (1978); Alauddin and Raza (1981) Malik and Saqib… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…Bayraktar and Moreno-Dodson (2015), Moreno-Dodson (2008), and Afonso et al (2006) examine the growth impact of public spending and determine that economic growth is negatively affected by public spending that successively distresses the distribution of income. Shirazi et al (2001) examine the impact of fiscal policy on income distribution in Pakistan. They use microdata from the Household Integrated Economic Survey (HIES).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Bayraktar and Moreno-Dodson (2015), Moreno-Dodson (2008), and Afonso et al (2006) examine the growth impact of public spending and determine that economic growth is negatively affected by public spending that successively distresses the distribution of income. Shirazi et al (2001) examine the impact of fiscal policy on income distribution in Pakistan. They use microdata from the Household Integrated Economic Survey (HIES).…”
Section: Literature Reviewmentioning
confidence: 99%
“…A variety of literature exists on fiscal policy and its impact on poverty and income inequality. Shirazi et al (2001) used the micro data from Household Integrated Economic Survey to see the redistributive effect of fiscal policy in Pakistan. Fiscal policy was incorporated in the analytical model in the form of public expenditures and taxes.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It had a positive impact on income inequality, while on the other hand, there was a negative relationship between income inequality and fiscal policy multiplier. Shirazi et al (2001) found the impact of public expenditures and public taxes on income distribution in rural and urban areas of Pakistan. The data had been taken from HIES 1992-93.…”
Section: Introductionmentioning
confidence: 99%